2017
DOI: 10.1186/s40104-017-0158-4
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance and gestational effort in relation to dietary fatty acids in guinea pigs

Abstract: BackgroundDietary saturated (SFAs) and polyunsaturated (PUFAs) fatty acids can highly affect reproductive functions by providing additional energy, modulating the biochemical properties of tissues, and hormone secretions. In precocial mammals such as domestic guinea pigs the offspring is born highly developed. Gestation might be the most critical reproductive period in this species and dietary fatty acids may profoundly influence the gestational effort. We therefore determined the hormonal status at conception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…Moreover, Kowalska (2008) found that the female rabbits fed a complete diet fish oil (n-3) supplemented had a quantitavely and qualititavely better milk fat content, higher fertility prolificacy values, and higher body weight of young rabbits at birth. The observed effects in this study regarding the increase of litter size, fertility and higher body weight at birth support the conclusion of Nemeth et al, (2017) who recorded that PUFAs supplementation may contribute to an adjustment of energy accumulations to the total litter mass, which may both favor a mother's body condition at parturition and perhaps increase the offspring survival at birth.…”
Section: Reproductive Performancesupporting
confidence: 88%
“…Moreover, Kowalska (2008) found that the female rabbits fed a complete diet fish oil (n-3) supplemented had a quantitavely and qualititavely better milk fat content, higher fertility prolificacy values, and higher body weight of young rabbits at birth. The observed effects in this study regarding the increase of litter size, fertility and higher body weight at birth support the conclusion of Nemeth et al, (2017) who recorded that PUFAs supplementation may contribute to an adjustment of energy accumulations to the total litter mass, which may both favor a mother's body condition at parturition and perhaps increase the offspring survival at birth.…”
Section: Reproductive Performancesupporting
confidence: 88%
“…Reproduction is a costly process [ 1 4 ] and is directly linked to the evolution of reproductive strategies [ 5 ] and population dynamics [ 6 ]. In female mammals, reproduction is the most energetically demanding life-history phase [ 7 ], so it is firmly regulated by body condition and food availability [ 8 ]. Of the reproductive processes, lactation is the most energetically demanding for female mammals; it results in maximum metabolic rates and energetic costs [ 1 , 2 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although hypothetical ratio of the X chromosome‐bearing (X) and Y chromosome‐bearing (Y) spermatozoa is 1:1 after spermatogenesis, the actual sex ratio at birth is not often equal (Baxter et al., 2012; Johnson et al., 1988). Several factors are associated with sex ratio alteration, including birth weight (Vazquez‐Gomez et al., 2018), nutrition (Nemeth et al., 2017), season of birth, diseases and stress (Rorie, 1999), different levels of hormones (James, 2001) and time of insemination relative to ovulation (Soede et al., 2000); hence, the actual sex ratio at birth is difficult to predict or control. Sex preselection technology using flow cytometry has been developed and combined with artificial insemination (AI) to improve production efficiency and facilitate livestock management (Amann, 1999; DeJarnette et al., 2009; Garner, 2006).…”
Section: Introductionmentioning
confidence: 99%